COMPARAÇÃO ENTRE O MECDR E O MECID NA SOLUÇÃO DE PROBLEMAS DE AUTOVALOR - Loeffler, Carlos Friedrich; Frossard, Abraão Lemos Caldas; Lara, Luciano de Oliveira Castro; Bulcão, André (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This article compares the performance of two formulations of the BEM to solve acoustic problems, governed by the Helmholtz equation: the formulation of Dual Reciprocity and formulation with Direct Integration. The latter is a new alternative to the Dual Reciprocity technique for solving problems modeled by non-adjoint differential operators. Both method are similar, but, the formulation with Direct Integration is simpler and closely resembles an interpolation procedure. Thus, through the solution of eigenvalue problem,natural frequencies are calculated and their accuracy is taken as a parameter to assessing the quality of the results of each formulation. Examples whose analytical solution is known were chosen for analysis of the results.